Crescimento e produtividade de duas cultivares de feijão em função de doses de ácido 2,3,5-triiodobenzoico - Soratto, Rogério Peres [UNESP]; de Souza-Schlick, Genivaldo David; Fernandes, Adalton Mazetti [UNESP]; Antunes de Oliveira, Luís Fernando Fontana [UNESP] (FapUNIFESP (SciELO), 2015)
The excessive aboveground growth of common bean can increase plant lodging and promote very rapid canopy closing, limiting grain yield. The use of growth regulators, such as 2,3,5-triiodobenzoic acid (TIBA), can reduce plant growth, however, there is no information on the use of this technology in the common bean crop. The objective of this study was to evaluate the effect of TIBA rates (0, 8, 16, 32, 64, and 128g a.i. ha-1) on growth and grain yield of two common bean cultivars (‘IAC Alvorada’ and ‘IAC Jabola’). The experimental design used was randomized blocks, in a split plot scheme, with four replications. The application of TIBA reduced the stem length of both cultivars, to the average estimated rate of 100 g ha-1 TIBA. Height of insertion of the first pod was reduced only in IAC Alvorada up to rate of 88 g ha-1 TIBA. Application of TIBA reduced by 10% the number of grains per pod. The use of TIBA did not affect grain yield, being an alternative to reduce the size of the common bean plants.
Growth and yield of two common bean cultivars as affected by 2,3,5-triiodobenzoic acid rates
Keywords: Growth regulators; Phaseolus vulgaris; Plant height; Yield components